KEBIJAKAN POLITIK LUAR NEGERI INDONESIA DALAM INTEGRASI KERJASAMA DI ASEAN UNTUK MENYIKAPI PERMASALAHAN PEREDARAN NARKOBA - Alfiyah, Nur Inna; Triandika, Lulus Sugeng (Global and Policy Journal of International Relations, 2018)
This article seeks to explain the Indonesian foreign policy in the integration of ASEAN cooperation related to the handling of drugs and drug trafficking. Illegal trade in drugs/hazardous materials in the form of narcotics or abbreviated Narcotics, is a challenge for the Indonesian government because it can threaten national security. This threat requires the government to increase regional and international vigilance and cooperation in handling drug problems optimally and effectively.Keywords: transnational crime, foreign policy, ASEAN integration cooperationDOI: https://doi.org/10.33005/jgp.v6i02.1819